Manajmen Program Tahfidzul Qur’an Dalam Meningkatkan Hafalan Santri Di Pondok Pesantren Al-Ikhwan Topoyo Kabupaten Mamuju Tengah - Abdul Malik; Syamsidar Syamsidar; Andi Sumardin (Education and Learning Journal, 2022)
This research is motivated by the phenomenon of the development of Islamic boarding schools as a forum for the community to include their children as hafidz Qur'an but there are several problems encountered, namely related to management in the management, this study aims, namely: 1) To find out how the management of the tahfidz program in improving student memorization at the Al-Ikhwan Topoyo Islamic Boarding School, 2) To determine the inhibiting and supporting factors of the tahfidz program in improving santri memorization at the Al-Ikhwan Topoyo Islamic Boarding School. In compiling this research, there are several theories that are used as the basis for researchers' policies in conducting research, it will be an instrument to see whether the theory is in accordance with the facts on the ground, therefore this type of research is qualitative research with the method used is the qualitative descriptive. Based on the results of the study, the management of the tahfidz program at Al-Ikhwan has been regulated as well as the activities in the cottage starting from dawn at 03.30 until evening at 21.30. The inhibiting factors of the tahfidzul Qur'an program in improving the memorization of students at the Al-Ikhwan Topoyo Islamic boarding school are a special place for memorizing the Qur'an, time management, the laziness of some students, and the food consumed. While the supporting factors are: an Islamic environment, avoiding cellphones/gadgets, and applying methods that can strengthen students' memorization.